Retention and storage stability of vitamins A and C in extruded native and pregelatinized starches - Abdul Manan, Siti Farhiah (2015)
A study was carried out to determine the retention of vitamins A and C in native and pregelatinized starches extruded under fixed conditions in the making of extruded dried noodles. Two percent vitamin A or C was mixed with starch and moisture content of the mixture was adjusted to 20% before extrusion. The extrusion conditions were temperatures of 80 °C for zone 1 and 100 °C for zones 2, 3 and 4 of the barrel, 30 rpm of feeder speed, and 60 rpm of screw speed. Native starches used were waxy corn (99.1% amylopectin), regular corn (26.2% amylose), high amylose corn (70.0% amylose), waxy potato (99.1% amylopectin), regular potato (30.1% amylose), waxy or glutinous rice (92.6% amylopectin), regular rice (19.4% amylose), tapioca (25.9% amylose), sweet potato (29.9% amylose) and sago (30.4% amylose) starches. The pregelatinized starches included pregelatinized waxy corn, regular corn, high amylose corn, waxy potato, regular potato, waxy or glutinous rice, regular rice,tapioca, sweet potato and sago starches. The retention of vitamins A and C,after extrusion, was analysed by reversed-phase high performance liquid chromatography (RP-HPLC). The results obtained showed that the extrusion conditions employed were able to retain high levels of vitamins A (86.7 to 93.4%) and C (88.4 to 98.6%) in all the extruded native starches. Within similar group of native starch source of corn, potato and rice, vitamins A and C retention was significantly higher in extruded waxy corn, potato and rice than in their extruded regular and high amylose starches. In extruded pregelatinized starches, the retention of vitamins A and C was significantly improved compared to that of their extruded native starches counterparts. Vitamin A concentration in extruded pregelatinized starches was the highest in extruded pregelatinized waxy corn (11.363±0.25 mg/g) and the lowest in extruded pregelatinized regular potato (8.447±0.13 mg/g). Extruded pregelatinized waxy corn also retained the highest vitamin C concentration (19.376±0.16 mg/g) while the lowest concentration was found in extruded pregelatinized high amylose corn starch (16.467±0.27 mg/g). Storage stabilities and determination of degradation kinetics of vitamins A and C in extruded native and pregelatinized starches were conducted at 25 °C in aluminium and nylon packagings. Degradation constant (k) of vitamin A was lower in pregelatinized starches as compared to that in their native counterparts, ranging from 5.18 to 8.67×10-2/week in aluminium packaging and 5.43 to 10.02×10-2/week in nylon packaging. Similar pattern was observed for vitamin C with its degradation constant (k) ranging from 3.55 to 5.56×10-2/week in aluminium packaging and 3.94 to 5.77×10-2/week in nylon packaging. It was observed that vitamins A and C in extruded starches were more stable in aluminium packaging than in nylon packaging as represented by the smaller degradation constant (k). It can be concluded that in all the extruded starches, the stability during extrusion and upon storage was significantly higher for vitamin C than vitamin A. The findings provided information on the application of the fixed extrusion conditions for better retention of vitamin A or vitamin C in starches. Their stabilities in aluminium packaging and pregelatinized starches suggested that both vitamins were sensitive to light and air present in porous pregelatinized starch extrudates respectively.